Comparison of Left Atrial Bipolar Voltage and Scar Using Multielectrode Fast Automated Mapping versus Point‐by‐Point Contact Electroanatomic Mapping in Patients With Atrial Fibrillation Undergoing Repeat Ablation. (10th January 2017) - LIANG, JACKSON J.; ELAFROS, MELISSA A.; MUSER, DANIELE; PATHAK, RAJEEV K.; SANTANGELI, PASQUALE; SUPPLE, GREGORY E.; SCHALLER, ROBERT D.; FRANKEL, DAVID S.; DIXIT, SANJAY
Voltage Differences With Multielectrode Mapping: Introduction: Bipolar voltage criteria to delineate left atrial (LA) scar have been derived using point‐by‐point (PBP) contact electroanatomical mapping. It remains unclear how PBP‐derived LA scar correlates with multielectrode fast automated mapping (ME‐FAM) derived scar. We aimed to correlate scar and bipolar voltages from LA maps created using PBP versus ME‐FAM. Methods and Results: In consecutive patients undergoing repeat AF ablation, 2 separate LA maps were created using PBP and ME‐FAM during sinus rhythm before ablation. Contiguous areas in the LA with a bipolar voltage cutoff of ≤0.2 mV represented dense scar; LA scar percentage was calculated for each map. Each LA shell was divided into 9 regions and each region further subdivided into 4 quadrants for additional analysis; mean voltages of all points obtained using PBP versus ME‐FAM in each region were compared. Forty maps (20 PBP: mean 228.5 ± 95.6 points; 20 ME‐FAM: 923.0 ± 382.6 points) were created in 20 patients. Mapping time with ME‐FAM was shorter compared with PBP (13.3 ± 5.3 vs. 34.4 ± 13.1 minutes; P < 0.001). Mean LA scar percentage was higher with PBP compared with ME‐FAM (15.5 ± 17.1% vs. 12.8 ± 17.6%; P = 0.04). Mean PBP voltage distribution was lower (compared with ME‐FAM) in the septum (0.95 ± 0.73 vs. 1.46 ± 0.99 mV; P = 0.009), posterior wall (0.84 ± 0.42 vs. 1.40 ± 0.83 mV; P = 0.0008), roof (0.78 ± 0.80 vs. 1.39 ± 1.09 mV; P = 0.0003), and right PV–LA junction (0.34 ± 0.25 vs. 0.59 ± 0.50 mV; P = 0.01) regions, while voltages were similar in all other LA regions (all P > 0.05). Conclusions: In AF patients undergoing repeat ablation, bipolar voltage is greater in certain LA segments with ME‐FAM compared with PBP mapping.